(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2007)
The present paper analyses mycotoxin contamination in six oil flax seed of the flax varieties differing in the length of the growing season. The flax seed grown in precision field trials was analyzed for mycotoxin contamination at harvesting and during storage period.The analyses done at harvesting revealed the traces of aflatoxin were identified only in the seed samples of cvs. Lu-5 and Gold Merchant, while those of ochratoxin A (2.3 µg kg'1) in the seed sample of cv. Szaphir. All the seed samples tested were found positive for DON contamination, except for cv. Blue Chip, but the levels identified were very low. After 8 months of storage the levels of aflatoxin and ochratoxin A. in flax seed samples increased. Mycotoxin increasing immediately concerned with seed fungi contamination. These indicators could be determining by moisture control such as seed drying.